2015
DOI: 10.1152/japplphysiol.00884.2014
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of neurokinin-1 receptors in the ventral respiratory column does not affect breathing but alters neurochemical release

Abstract: Substance P (SP) and its receptor, neurokinin-1 (NK1R), have been shown to be excitatory modulators of respiratory frequency and to stabilize breathing regularity. Studies in anesthetized mice suggest that tonic activation of NK1Rs is particularly important when other excitatory inputs to the pre-Bötzinger complex in the ventral respiratory column (VRC) are attenuated. Consistent with these findings, muscarinic receptor blockade in the VRC of intact goats elicits an increase in breathing frequency associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…This instability contrasts to studies (Langer et al, 2016; Muere et al, 2013, 2015a; Muere et al, 2015b; Muere et al, 2015c) in which dialyses of antagonists to multiple excitatory receptors in the VRC did not destabilize breathing. The destabilization with DAMGO could be due to time-dependent changes in the direct effect of opioid-induced depression and the indirect effect of potential compensatory mechanisms.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…This instability contrasts to studies (Langer et al, 2016; Muere et al, 2013, 2015a; Muere et al, 2015b; Muere et al, 2015c) in which dialyses of antagonists to multiple excitatory receptors in the VRC did not destabilize breathing. The destabilization with DAMGO could be due to time-dependent changes in the direct effect of opioid-induced depression and the indirect effect of potential compensatory mechanisms.…”
Section: Discussioncontrasting
confidence: 95%
“…The current and past dialysis studies in unanesthetized goats found neuromodulator compensation during perturbation of G protein-coupled receptors (Muere et al, 2013, 2015a; Muere et al, 2015b; Muere et al, 2015c). Herein we found what could be interpreted as overcompensation for increases in inhibitory ionotropic GABA receptor activity during muscimol dialysis.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations